Effects of mixed feeding schedules on growth performance, body composition, and nitrogen- and phosphorus balance in rainbow trout, Oncorhynchus mykiss - H. Sevgili; Y. Emre; M. Kanyilmaz; I. Diler; B. Hoĺľsu (Acta Ichthyologica et Piscatoria, 2006)
Background. Reducing feed cost and the pollution originating from feed have been principal matters in fish nutrition. Mixed feeding schedules have been proposed as one of the methods to reduce both of them and successfully tested in many fish species. The aim of the present study was to determine the mixed feeding schedules′ suitability for culture of rainbow trout. Materials and methods. Five different feeding schedules were tried by alternating the presentation of a low-protein (28.1%) diet (A) and a high-protein (49.9%) diet (B). The feeding schedules employed were 1A/1B, 1A/2B, 1A/3B, 2A/2B, and 2A/3B where the numerical values refer to the number of days each diet (A and B) was offered continuously. Fish given diets A and B continuously served as controls. Totally, seven dietary treatments were tested in triplicate for 10 weeks. Results. The fish maintained on the different mixed feeding schedules exhibited lower weight gain than those fed continuously on the high-protein diet (P < 0.05). The fish reared on schedule 1A/3B (1 day diet A alternated with 3 days diet B) had similar specific growth rate (SGR), feed conversation ratio (FCR), and protein efficiency ratio (PER) to those fed diet B continuously and was best among all mixed feeding schedules. However, the most cost-effective treatment was 2A/2B. In addition, this group compared to B resulted in significant increase and reduction of phosphorus retention and discharge, respectively (P < 0.05). The treatments significantly effected body moisture, fat- and ash levels (P < 0.05), but not protein. Conclusion. The study shows that mixed feeding schedules are promising for use in rainbow trout culture as they result in feed cost saving and reduced phosphorus discharge in the effluents.